Kinetics and Thermodynamics of Ultrasound-Assisted Depolymerization of κ-Carrageenan - Ratnawati Ratnawati; Aji Prasetyaningrum; Dyah Hesti Wardhani (Masyarakat Katalis Indonesia - Indonesian Catalyst Society (MKICS), 2016)
The ultrasound-assisted depolymerization of κ-carrageenan has been studied at various temperatures and times. The κ-carrageenan with initial molecular weight of 545 kDa was dispersed in water to form a 5 g/L solution, which was then depolymerized in an ultrasound device at various temperatures and times. The viscosity of the solution was measured using Brookfield viscometer, which was then used to find the number-average molecular weight by Mark-Houwink equation. To obtain the kinetics of κ-carrageenan depolymerization, the number-average molecular weight data was treated using midpoint-chain scission kinetics model. The pre-exponential factor and activation energies for the reaction are 2.683×10-7 mol g-1 min-1 and 6.43 kJ mol-1, respectively. The limiting molecular weight varies from 160 kDa to 240 kDa, and it is linearly correlated to temperature. The results are compared to the result of thermal depolymerization by calculating the half life. It is revealed that ultrasound assisted depolymerization of κ-carrageenan is faster than thermal depolymerization at temperatures below 72.2°C. Compared to thermal depolymerization, the ultrasound-assisted process has lower values of Ea, ΔG‡, ΔH‡, and ΔS‡, which can be attributed to the ultrasonically induced breakage of non-covalent bonds in κ-carrageenan molecules.